Analisis Pengelolaan Zakat Fitrah Masjid Paripurna Nurul Ibadah Kecamatan Tenayan Raya Kota Pekanbaru - Ifan Saputra; Daharmi Astuti (LPMP Imperium, 2021)
The purpose of this study was to determine the management of zakat fitrah at the Paripurna Nurul Ibadah Mosque, Tenayan Raya District, Pekanbaru City. The data collection technique used is the documentation technique, namely the systematic analysis of qualitative data (Observation, Interview, and Documentation). The results of this study indicate that the management and distribution of zakat fitrah at the Nurul Ibadah Plenary Mosque has met the management standards of zakat fitrah, but in the aspect of the collection, there are still muzakki who pay their zakat fitrah outside the mosque. As for the zakat fitrah distribution system, technically, muzakki delivers to amail, amil picks up the muzakki's house, muzakki transfers his zakat account to the mosque. The collection technique is like money/rice if it is in a percentage of 2.5%. Meanwhile, the zakat fitrah distribution is carried out for the congregation of the Nurul Ibadah Mosque congregation by UPZ, distributed five days before Eid; the maximum time is on the eve of Eid al-Fitr